An overview on the RSV-mediated mechanisms in the onset of non-allergic asthma - Manti, Sara; Piedimonte, Giovanni (Frontiers in Pediatrics, 2022)
Respiratory syncytial virus (RSV) is recognized as an important risk factor for wheezing and asthma, since it commonly affects babies during lung development. Whether the role of RSV in the onset of atopic asthma is widely recognized, its impact on the onset of non-atopic asthma, mediated via other and independent causal pathways, has long been also suspected, but the association is less clear. Following RSV infection, the release of local pro-inflammatory molecules, the dysfunction of neural pathways, and the compromised epithelial integrity can become chronic and influence airway development, leading to bronchial hyperreactivity and asthma, regardless of atopic status. After a brief review of the RSV structure and its interaction with the immune system and neuronal pathways, this review summarizes the current evidence about the RSV-mediated pathogenetic pathways in predisposing and inducing airway dysfunction and non-allergic asthma development.